Variation in the Immunoregulatory and Antiviral Cytokine mRNA Levels between Lentogenic and Velogenic Pathotypes of Avian Orthoavulavirus-1 - Rajasekaran, Ranjani; John, John Kirubaharan; Chandran , N Daniel Joy (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Future strategies to control Avian Orthoavulavirus-1 (AOaV-1), the causative agent of Newcastle disease (ND) in poultry, would rely extensively on virus-host interactions. Cytokines, the molecular messengers of immune system, are considered a significant entity in understanding the complex interplay between virus and host immune response. In the present study, the mRNA levels of immunoregulatory (IFN-γ and IL-12) and antiviral (IFN-α and IFN-β) cytokines were studied in in-vitro (chicken embryo fibroblast cells - CEF) and in-vivo (spleen of chicken) systems in response to lentogenic (D58) and viscerotropic velogenic (D165) AOaV-1 at five time points after experimental infection (1, 2, 3, 4 and 5 days post-infection). The mRNA levels of immunoregulatory and antiviral cytokines varied significantly between lentogenic D58 and velogenic D165 across both the systems at all time points under study. It was significantly upregulated for velogenic D165 when compared to lentogenic D58. This significant difference indicated that induction of cytokinesis unique for different pathotypes of AOaV-1, thereby highlighting the importance of studying cytokine mRNA levels to understand molecular pathogenesis of AOaV-1.